Analyzing the Changing Role of Professional Secretary in Dealing with The Impact of Digital Technology (A Case Study on Professional Secretaries in Indonesia) - Bertha Musty (Research Collaboration Community (RCC), 2023)
The purpose of this research is to analyze the preparedness of secretaries’ profession in dealing with the changing role in handling administrative work and the other impacts of digital technology. The research objectives are to determine the understanding of digital technology in business administration that will have an impact on the automation and simplification of secretarial administrative work, to find out what executive secretary jobs can be replaced by the digital technology and to identify competences of the secretary. This study was carried out using descriptive qualitative methodology with online survey technique with total respondents of 150 Professional Secretaries from various companies in Indonesia, and an addition of 25 respondents, who are superiors of secretaries. The research concludes that several secretarial jobs have been supported by some developing digital technology tools. Digital technology helps increase the efficiency of secretarial administrative task, as much as 56% in document filing management, 76% in managing database, 70% in analyzing data and information, 47% in implementing and maintaining administration procedures. It helps track and streamline processes. In fact, this increased efficiency in operation helps reduce costs and time, 52% in organizing meeting, 82% in maintaining diaries, 47% in arranging manager’s business travel. This research proposes new competencies of professional secretary that need to be strengthened, specifically in the areas of the digitalization and automation secretarial administrative tasks, management office information system, data analysis, communication, and public relations function. This topic of digital technology in secretarial administrative work in Indonesia has never been discussed before. It has a substantial impact on developing secretarial profession in Indonesia and gives a boarder impact on the preparedness of development the executive secretary role in companies.